The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/13645706.2017.1407798
|View full text |Cite
|
Sign up to set email alerts
|

A concept for electromagnetic navigated targeting of liver tumors using an angiographic approach

Abstract: The initial methodology of the proposed technique was confirmed to be feasible, introducing a novel concept for simple and precise navigated targeting of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The reported effective end-to-end targeting errors range between 3–8 mm for in vitro and in vivo measurements [ 27 , 29 , 32 , 33 ]. We have previously reported target positioning errors below 3 mm when applying the herein proposed navigation approach in an ex vivo setting [ 20 ], and now showed similar targeting accuracies of 2.6 ± 1.6 mm for baseline measurements in vivo. This represents the best possible end-to-end accuracy when applying the proposed technique in an angiographic setting, and thus describes the inherent errors when using EM tracking in this environment.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The reported effective end-to-end targeting errors range between 3–8 mm for in vitro and in vivo measurements [ 27 , 29 , 32 , 33 ]. We have previously reported target positioning errors below 3 mm when applying the herein proposed navigation approach in an ex vivo setting [ 20 ], and now showed similar targeting accuracies of 2.6 ± 1.6 mm for baseline measurements in vivo. This represents the best possible end-to-end accuracy when applying the proposed technique in an angiographic setting, and thus describes the inherent errors when using EM tracking in this environment.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, no EM tracked device for thermal ablation is currently available, although the advantage of using ablation probes tracked at their tip have been reported ex vivo and in vivo [ 29 , 43 , 44 ]. However, other EM tracked devices such as EM tracked trocars would be readily available for clinical use and have shown similar targeting accuracies in our ex vivo experiments [ 20 ]. Ultimately, this study did not include any aspects regarding local ablative treatment or outcomes beyond tumor targeting, and focused solely on the accuracy and efficiency of ablation probe positioning.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on lesion tracking using electromagnetic (EM) trackers have shown promising results. [17][18][19][20] Most of these EM trackers are wired, which requires intraoperative implantation and subsequent intraoperative imaging to locate the tracker relative to the lesion after which the system can be calibrated. These intraoperative steps consume intraoperative time and hamper surgical workflow.…”
mentioning
confidence: 99%